3D-printed apparel and 3D-printer: exploring advantages, concerns, and purchases. Issue 1 (2nd January 2018) - Perry, Anna
ABSTRACT: The purpose of this study was to examine consumer perceptions of 3D-printed apparel and 3D-printers, in terms of (1) advantages, (2) concerns, and (3) purchasing. Thirteen respondents participated in the structured in-depth interviews. A phenomenological interpretation method was used to analyse the data. The results indicated that for 3D-printed apparel, participants were more interested in accessories than clothing; unlike previous studies' proposals, 3D-printed apparel may be not sustainable and cheap; and the advantages (e.g. customisation and fit) were not the main reasons for buying, but the concerns (e.g. not comfortable and not ease of movement) were the dominant reasons for not buying. For 3D-printers, consumers mostly perceived advantages. The advantages (e.g. convenient, fast, and good for consumer, small business, and co-design) influenced their purchase intentions.